Biologic Therapies for Type 2 Inflammatory Diseases: A Bibliometric Analysis of Publication Trends and Intellectual Structure - Gerek, Mehmet Emin; Önalan, Tuğba (The European Research Journal, 2026)
Objectives: To comprehensively analyze the scientific literature (2005–2025) on biologic agents for Type 2 inflammatory diseases, including Severe Asthma (SA), Atopic Dermatitis (AD), and chronic rhinosinusitis with nasal polyps (CRSwNP). This study aimed to identify publication trends, thematic clusters, collaboration networks, and the field’s intellectual foundation. Methods: A bibliometric analysis was performed using data from the Web of Science (WoS) Core Collection (retrieved October 27, 2025). VOSviewer software was used to analyze co-occurrence networks (based on Author Keywords) and map collaborations. Results: A total of 7,339 publications were analyzed. A significant acceleration in publishing occurred after 2017. The most productive countries were the USA (n=2,346), Italy (n=1,149), and the UK (n=936). Thematic analysis identified three distinct clusters: AD, SA, and CRSwNP. The intellectual foundation of the field is built upon highly cited phase 3 clinical trials (e.g., mepolizumab, dupilumab, benralizumab) published in top-tier journals (NEJM, The Lancet). Conclusions: The research landscape for Type 2 biologics has grown rapidly since 2017, driven by clinical validation in landmark trials. The field’s focus is evolving from demonstrating clinical efficacy toward mechanism-based personalized medicine and biomarker identification.